Polyols and polyurethane foams from acid‐catalyzed biomass liquefaction by crude glycerol: Effects of crude glycerol impurities. Issue 18 (8th April 2014) - Hu, Shengjun; Li, Yebo
ABSTRACT The effects of crude glycerol impurities on acid‐catalyzed biomass liquefaction by crude glycerol were investigated. Salts (i.e., NaCl and Na2SO4) decreased biomass conversion ratios and negatively affected the properties of polyols produced. Regression models were developed and validated as appropriate for describing the relationships between organic impurities and biomass conversion ratios and between organic impurities and the hydroxyl number of polyols. Polyols produced from crude glycerol containing 0–45% organic impurities showed the hydroxyl number varying from 1301 to 700 mg KOH/g, acid number from 19 to 28 mg KOH/g, viscosity from 2.4 to 29.2 Pa s, and molecular weight (Mw) from 244 to 550 g/mol. Crude glycerol containing 40–50 wt % of organic impurities was suitable to produce polyols with suitable properties for rigid and/or semi‐rigid polyurethane (PU) foam applications. The produced PU foams showed density and compressive strength comparable to those derived from petrochemical solvent‐based liquefaction processes. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40739.